Geology and Wine 4. The Origin and Odyssey of Terroir - Wilson, James (Geoscience Canada)

(untitled) (The Geological Association of Canada, 2001)
Summary As a wine term terroir dates from the glorious years of 14th century wine-making in Burgundy, France. The term was first applied to certain top-quality wine-producing properties along the Côted'Or, Burgundy. Outside France terroir is being applied more loosely, to properties producing less than top-quality wines, not the original purpose of the term. Terroir recognizes many of the physical elements of wine-making, including good drainage,soil structure, nature of clays, and the existence and interaction of chemical compounds such as calcium carbonate, iron, magnesium, and others in an almost mysterious alchemy in the wine-growing process. Although the physical and chemical interactions that affect the growing of wine are not well understood, the spread of the term terroir is encouraging better use of geology, soil, climate, and culture in producing better wines.